2011
DOI: 10.1016/s0377-1237(11)60052-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy in free flap surgery: is it meaningful?

Abstract: Routine use of hyperbaric oxygen therapy does not result in better survival of free flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…A total of 29 studies using HBOT for skin wound healing were included . Fourteen studies investigated HBOT for chronic wounds, 12 studies investigated HBOT in acute wounds, one study investigated HBOT in both chronic and acute wounds and two studies were performed in experimental wound models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 29 studies using HBOT for skin wound healing were included . Fourteen studies investigated HBOT for chronic wounds, 12 studies investigated HBOT in acute wounds, one study investigated HBOT in both chronic and acute wounds and two studies were performed in experimental wound models.…”
Section: Resultsmentioning
confidence: 99%
“…Vishwanath investigated the effects of HBOT on free flaps. 56 Flap survival, flap edema, venous congestion, and period of postoperative recovery were evaluated. None of these findings were significantly different.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Incluyeron 8 estudios, involucrando pacientes con quemaduras agudas 44,45 , heridas por trauma 46 , quemaduras por radiación ultravioleta 47 , colgajos libres 48 , injertos de piel parcial 42 y postoperados de lifting facial 49 y reducción mamaria post radioterapia 50 . Siete de los 8 estudios favorecieron el uso de la cámara hiperbárica.…”
Section: Evidencia De Ensayos Clínicosunclassified
“…The operative technique requires involves vascular anastomosis and requires special instrumentation, Operative magnification, and training. 4,5 Antithrombotic agents such as low molecular-weight dextran, aspirin and heparin have been thought to play a significant role in this success. Ninety-six percent of micro surgeons use antithrombotic agents such as dextran, heparin and aspirin alone or combination in free flap transfer and replantation.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of reports of significant morbidity and mortality related to these agents have brought into question their routine use in microsurgery. 3,4 Their adverse effects can cause morbidity and mortality in patients; with serious side effects from low-molecularweight dextran have been reported. For example, Disa and colleagues reported that dextran did not improve benefit in free flap survival but increased the risk of systemic complications.…”
Section: Introductionmentioning
confidence: 99%